Association of Body Mass Index in Youth With Adult Cardiometabolic Risk - Wu FT; Juonala M; Sabin MA; Buscot MJ; Pahkala K; Smith KJ; Hutri-Kahonen N; Kahonen M; Laitinen TP; Viikari JSA; Raitakari OT; Magnussen CG (WILEY, 2025)
Background: Whether long-term exposure to overweight or obesity from early life to adulthood has a detrimental influence on health outcomes is unknown. We aimed to investigate whether duration of overweight or obesity from youth to adulthood is associated with adult cardiometabolic risk.
Methods and Results: A population-based cohort study was performed of 1268 youths, aged 3 to 18 years, with follow-ups at 3, 6, 9, 12, 21, 27, and 31 years. Duration of overweight or obesity over 31-year follow-up was calculated. Adulthood outcomes included type 2 diabetes mellitus, impaired fasting glucose, high insulin levels, high carotid intima-media thickness, hypertension, low high-density lipoprotein cholesterol, high low-density lipoprotein cholesterol and triglycerides, arterial pulse wave velocity, carotid artery compliance, Young elastic modulus, and stiffness index. Rates of overweight/obesity were 7.9% at baseline and 55.9% after 31 years. After adjustment for confounders, longer duration of overweight or obesity was associated with increased risk of all outcomes (relative risk ranged from 1.45-9.06 for type 2 diabetes mellitus, impaired fasting glucose, carotid intima-media thickness, hypertension, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides; beta from 0.370-0.543 m/s for pulse wave velocity; -0.193 to -0.237 %/10 mm Hg for carotid artery compliance; 52.1-136.8 mm Hg center dot mm for Young elastic modulus; and 0.554-0.882 for stiffness index). When body mass index was further adjusted, these associations disappeared or were substantially reduced. Detrimental associations of adult body mass index with all outcomes were robust to adjustment for confounders and duration of overweight or obesity.
Conclusions: Overweight or obesity in adulthood rather than childhood appears to be more important for adult cardiometabolic health.